Synergistic effect of inthrathecal fentanyl and bupivacaine in spinal anesthesia for cesarean section in Baghdad city - Habasha, Zainab Faisal (International Journal Of Community Medicine And Public Health, 2022)
Background: Potentiating the effect of intrathecal local anesthetics drugs by addition of intrathecal opiods for intra-abdominal surgeries had been used lately. In this study by addition of fentanyl, we tried to minimize the dose of bupivacaine thereby reducing the side effect caused by higher doses of intrathecal bupivacaine in cesarean section, and to improve the quality of block. Methods: Study was performed on sixty patients underwent cesarean section they were divided into 6 groups as B10, B 12.5, B15 mg of bupivacaine and FB10, FB12.5, FB15 received a combination of 25 µg intrathecal fentanyl respectively, the parameter taken into consideration were visceral pain, hemodynamic stability (hypotension and bradycardia) intra operative sedation, nausea, vomiting and post-operative pain. Results: Onset of sensory block to T6 occurred faster with increasing bupivacaine doses in bupivacaine only groups and bupivacaine fentanyl combination groups. Alone lower concentration of bupivacaine could not completely remove the visceral pain. Blood pressure declined with increasing the concentration of bupivacaine and fentanyl. The incidence of nausea and vomiting was reduced significantly while post-operative pain relief and hemodynamics stability increased by adding fentanyl. Pruritis, maternal respiratory depression and changes in APGAR score of babies did not occur with fentanyl. Conclusions: Spinal anesthesia among the neuro axial blocks in obstetric patients’ needs strict dose calculation because minimal dose changes results in more complications and side effects Here the synergistics potentiating effects of fentanyl (an opiod) on bupivicaine (local anesthetic) in spinal anesthesia for cesarean section is presented. Fentanyl is able to reduce a dose of bupivicaine and therefore its harmful effect.